ANALISIS KINERJA KEUANGAN USAHA TAHU â€“ TEMPE â€œWENWINâ€ DI DESA SEA KECAMATAN PINELENG KABUPATEN MINAHASA - Winanda Pangestu; Vicky R.B. Moniaga; Theodora M. Katiandagho; Olfie L.S. Benu (COCOS, 2015)
ABSTRACT Â Winanda Pangestu. Financial Performance Analysis of Tahu â€“ Tempe Business â€œWenwinâ€ at Sea Village Pineleng Subdistrict of Minahasa Regency (under the guidance of Vicky R.B. Moniaga, as a Chairman, and Theodora M. Katiandagho and Benu Olfie L.S. as Members). The objective of this reserch to determine the financial performance of the Tahu â€“ Tempe business "Wenwin" based on the level of liquidity, solvency, and profitability. The study was conducted for four months starting from February 2015 until May 2015 at the Tahu â€“ Tempe Business "Wenwin" Sea Village Pineleng Subdistrict of Minahasa Regency. The data used in this study are primary data obtained directly from the Tahu â€“ Tempe business "Wenwin". Data collection was done by interview directly to the owner of the business. Analysis of the data used is descriptive analysis presented in the form of financial statement balance sheet and income statement were then analyzed by looking at the ratio of financial ratios. The research results showed that Tahu â€“ Tempe business "Wenwin" has a very good financial performance, seen from the measurement of financial ratios, liquidity ratios in 2013 is based on the measurement of the current ratio of 5.16 and a quick ratio of 5.15 measurement results and in 2014 current ratio increased to 22.92 and quick ratio increased to 22.91. The solvency ratio in 2013 showed that debt financing as much as 14%, and in 2014 decreased to 3% because most of the debt has been paid. The ratio of profitability by the year 2013 shows Gross profit margin amounted to 46 %, net profit margin of 37%, an ROI of 91% and a ROE of 107%. In 2014 gross profit margin decreased to 41%, net profit margin of 35%, an ROI of 64% and ROE of 67%. However it does not affect the ability of this business to make profits, because it is on a good criteria. Â Key Words : Financial Statement Analysis, Financial Ratio Analysis, Financial Performance